2015
DOI: 10.1111/joa.12365
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of human soft palate morphogenesis supports regional regulation of palatal fusion

Abstract: It is essential to complete palate closure at the correct time during fetal development, otherwise a serious malformation, cleft palate, will ensue. The steps in palate formation in humans take place between the 7th and 12th week and consist of outgrowth of palatal shelves from the paired maxillary prominences, reorientation of the shelves from vertical to horizontal, apposition of the medial surfaces, formation of a bilayered seam, degradation of the seam and bridging of mesenchyme. However, in the soft palat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 89 publications
(177 reference statements)
1
27
0
1
Order By: Relevance
“…Most of the present specimens were much later or larger than those used by Danescu et al (2015) who published an excellent study of soft palate development. Therefore, rather than palatogenesis, the present study concentrated onto a clear demonstration of anatomy of the nasopalatine duct.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…Most of the present specimens were much later or larger than those used by Danescu et al (2015) who published an excellent study of soft palate development. Therefore, rather than palatogenesis, the present study concentrated onto a clear demonstration of anatomy of the nasopalatine duct.…”
Section: Methodsmentioning
confidence: 85%
“…Epithelial pearls seemed to be classified into three types: (1) midline pearls originating from the midline epithelial seam of the palate; (2) paramedian pearls derived from the oral epithelium at Albrecht's incisive suture; and (3) lateral pearls arising from the dental lamina of all tooth buds. However, previous descriptions of epithelial pearls did not distinguish paramedian from other median and lateral pearls (Kitamura, 1991;Arnold et al, 1998;Danescu et al, 2015). Another disturbing factor in the fetal anterior palate is the developing vomer, as its lower part is likely to form a canal or space immediately above the incisive bone (Hansen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the presumptive vestibulum containing the nasal plug at stages 6 and 7 of the brown anole (Figs. 3 B and S 2 A) resembles a multilayered medial edge epithelial seam in the human embryonic soft palate (see [ 79 ]), although in the anole the basal layer, which forms the walls of the future vestibulum, can easily be distinguished. Distribution of the nasal plug is restricted to the vestibulum in later embryonic life [ 22 , 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The facial processes fuse at different times; maxillary – 6 weeks, upper lip – 8 weeks and palate – 12 weeks ( O’Rahilly, 1972 ; Danescu et al, 2015 ). Molecular studies have shown that the growth, structure and patternation of the facial primordia is controlled by a series of complex interactions that involves many factors such as fibroblast growth factors, sonic hedgehog proteins, bone morphogenetic proteins, homeobox genes Barx1 and Msx1 , the distal-less homeobox ( Dlx ) genes, and local retinoic acid gradients ( Barlow et al, 1999 ; Hu and Helms, 1999 ; Lee et al, 2001 ; Ashique et al, 2002 ; Mossey et al, 2009 ; Marcucio et al, 2015 ; Parsons et al, 2015 ).…”
Section: Pre- and Post-natal Facial Developmentmentioning
confidence: 99%